PERLINDUNGAN HUKUM BANK SYARI’AH TERHADAP WANPRESTASI NASABAH DALAM AKAD MUSYARAKAH DIHUBUNGKAN DENGAN PRINSIP SYARI’AH - Onin Iskandar; Dhody AR. Widjaja Atmadja; Refki Ridwan (Bajang Institute, 2025)
Musyarakah financing is a form of cooperation between two or more parties, in which Islamic banks entrust a certain amount of capital to the manager with a profit sharing agreement. However, in reality, Islamic banks are not free from the risk of losses caused by the sharia default. The problems studied in this thesis are First, What are the characteristics of the Islamic bank's musyarakah financing contract against the sharia? Second, How is the legal protection of Islamic banks against sharia default in the musyarakah financing contract related to sharia principles? The theories used in analyzing these problems are the contract theory and the legal protection theory.The method used in this study with the type of normative legal research, namely library legal research or secondary data with primary, secondary and tertiary legal materials sources. The research approach used is the legislative approach, conceptual approach, analytical approach, and case approach and the legal material collection technique is carried out by identifying and inventorying positive legal rules, book literature, journals and other legal sources. For the legal material analysis technique, it is carried out with grammatical and systematic legal interpretation while the legal construction method is with analogy and legal refinement.From the research results, it can be concluded that the characteristics of the musyarakah contract are cooperation between the bank and the customer with the principle of profit sharing where profits and losses are allocated according to the agreement, legal protection of Islamic banks against customer default in the musyarakah financing contract is by means of negotiation or selling the collateral object either voluntarily or through an auction mechanism, in order to pay off the customer's obligations.